Case Report: Coexistence of anti-LGI1 and anti-mGluR2 antibodies in an autoimmune encephalitis patient - Zhang, Xudong; Ma, Fei; Geng, Qingqing; Luo, Changjiang; Qu, Chuanqiang (Frontiers in Immunology, 2025)
Autoimmune encephalitis (AE) encompasses a broad group of inflammatory encephalopathies mediated by immune responses against central nervous system (CNS) antigens. With the expanding spectrum of identified anti-neuronal antibodies and their increasing clinical recognition, the number of confirmed AE cases has risen. Notably, cases involving concurrent positivity for multiple anti-neuronal antibodies have emerged, complicating both diagnosis and treatment. To date, no published reports have described the co-occurrence of anti-leucine-rich glioma-inactivated 1 (LGI1) antibody and anti-metabotropic glutamate receptor 2 (mGluR2) antibody in AE patients. We report a case of a 61-year-old woman presenting with impaired responsiveness, gait disturbance, and language disorders. Serological and cerebrospinal fluid (CSF) analyses revealed positivity for both LGI1 and mGluR2 antibodies. The anti-LGI1 antibody titers were 1:32+ (serum) and 1:1+ (CSF), while anti-mGluR2 antibody titers were 1:100+ (serum) and 1:10+ (CSF). Based on clinical manifestations and diagnostic findings, the patient was diagnosed with AE with concurrent anti-LGI1 and anti-mGluR2 antibody positivity. The patient received intravenous immunoglobulin (IVIG) and methylprednisolone pulse therapy (500 mg/day), resulting in symptomatic improvement. Following discharge, maintenance therapy with oral prednisone acetate and mycophenolate mofetil was initiated. At the one-week follow-up, her condition remained stable; however, she succumbed to death at the two-week follow-up due to complications from poor oral intake.